(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the life and scientific activities of Nabijon Boqiy, a talented writer and publicist of Uzbek literature. The aim of his life is to show the development of documentary journalism in Uzbek literature, as well as the further enrichment of the approach to issues of historical memory. The study analyzes existing sources in literary studies, memoirs, and popular scientific materials about the writer, and scientifically evaluates the life of Nabijon Boqiy as an important part of the Uzbek national literary process.